Involvement of intracellular Ca2+ stores in 3,4-diaminopyridine-evoked [3H]norepinephrine release. - Huang Hua-Yu; Zhou Cheng-Wen (Acta Pharmacologica Sinica; Vol 17, No 4 (July 1996): Acta Pharmacologica Sinica, 2016)
AIM: To study the mechanism for 3, 4-diaminopyridine (DAP) evoking external Ca(2+)-independent release of [3H] norepinephrine ([3H] NE). METHODS: Rat hippocampal slices were preincubated with [3H] NE and superfused with medium. [3H] NE release was determined. RESULTS: Under Ca(2+)-free conditions, DAP evoked [3H] NE release. In rats pretreated by reserpine, the effect of DAP was no longer detectable. Ca2+ chelator BAPTA-AM potently inhibited DAP-evoked [3H] NE release. Desipramine 100-500 mumol.L-1 strongly induced [3H] NE release in a concentration-dependent manner, whereas caffeine 30-70 mmol.L-1 was slightly effective on [3H]NE release. The blocker of Ca(2+)-induced Ca2+ releasable stores, dantrolene sodium did not attenuate DAP-evoked [3H]NE release. CONCLUSION: In the absence of extracellular Ca2+, DAP evokes exocytotic release of [3H]NE from synaptic vesicles through liberation of internal Ca2+ from inositol 1, 4, 5-trisphosphate-sensitive Ca2+ stores.